2020
DOI: 10.3390/molecules25225311
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Grape Seed and Skin Extracts and Their Influence on Biochemical Markers

Abstract: This review is focused on the study of the effects of grape seed and skin extract (GSSE) on human health. GSSE contains high concentrations of important polyphenolic substances with high biological activity. This review is a summary of studies that investigate the effects of GSSE on diabetes mellitus, cardiovascular disease and cancer, its neuroprotective effect, and its effects on the gastrointestinal tract and other health complications related to these diseases. The results of the studies confirm that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 82 publications
1
27
0
Order By: Relevance
“…15,17 In this regard, grapes, and especially their seeds and skin, represent one of the richest natural sources of antioxidant phenolic compounds. [18][19][20] Grape pomace, a mixture of seeds and skins obtained by pressing grapes, represents a by-product of wine production characterized by a relatively high concentration of phenolics, 21 being the skins rich in anthocyanins and the seeds in non-anthocyanin molecules. 22 The costeffective and sustainable conversion of the grape pomace into valuable antioxidant extracts is a "green" paradigm adopted in food, cosmetic, and pharmaceutical industries to reduce the environmental impact of waste disposal in winemaking.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 In this regard, grapes, and especially their seeds and skin, represent one of the richest natural sources of antioxidant phenolic compounds. [18][19][20] Grape pomace, a mixture of seeds and skins obtained by pressing grapes, represents a by-product of wine production characterized by a relatively high concentration of phenolics, 21 being the skins rich in anthocyanins and the seeds in non-anthocyanin molecules. 22 The costeffective and sustainable conversion of the grape pomace into valuable antioxidant extracts is a "green" paradigm adopted in food, cosmetic, and pharmaceutical industries to reduce the environmental impact of waste disposal in winemaking.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is not known if humans and rats process GSE polyphenols differently and hence generate different active metabolites. However, in a recent review of the health benefits in humans, dietary inclusion of grape seed and skin extracts was reported to be neuroprotective and beneficial in other diseases ( 72 ). In conclusion, data from our studies support the notion that inclusion of GSE as dietary supplement may offer a safe and beneficial complementary therapeutic option for migraine and other orofacial pain conditions whose pathology involves persistent central sensitization and dysfunction of the descending inhibitory pain modulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Grapeseed oil is rich in phenolic compounds and flavonoids. 5,9 These bioactive compounds were shown to exhibit significant antioxidant activities when incorporated into dermocosmetic formulations. 6,13 The findings of this study were consistent with those previously reported on the effects of antioxidants and other bioactive compounds on the skin melanin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in this study, the novel grapeseed oil‐loaded dermocosmetic nanoemulgel resulted in continuous and statistically significant decline in skin melanin levels. Grapeseed oil is rich in phenolic compounds and flavonoids 5,9 . These bioactive compounds were shown to exhibit significant antioxidant activities when incorporated into dermocosmetic formulations 6,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation